Analisis Yuridis Penyalahgunaan Data Pribadi Konsumen Pinjaman Online Di Indonesia (Studi Putusan Nomor 597/Pid.Sus/PN.Jkt.Pst) - Fachroji, Ferlin Muhammad (Jurnal Ilmiah Wahana Pendidikan, 2023)
Abstract The development of technology is developing very rapidly, including in debts, in terms of debts known as online loans that make it easier for debtor to obtain loans, but in practice, personal data from debtors as customers are often misused for creditors personal needs, this article aims to find out the legal basis and law enforcement of the misuse of this data, this research uses a normative juridical method with data collexted using library research, in which later it can be found what legal rules relate to the misuse of personal data and how to implement and enforce rhem using examples os cases that available on the decision study that was the focus of the research fot this article Keywords : Personal data, Misuse, Law Enforcement